Şafii mezhebinde mal kavramının gelişimi ve ilgili hükümlerin analizi - Ortaç, Gülsüm (My University, 2025)
İmam Şâfiî hayatının önemli bir bölümünü teşkil eden ilim yolculuğu ve arayışları neticesinde bugün kendisine izafe edilen mezhebinin temellerini atmıştır. Onun bu arayışları neticesinde fıkhî kanaatlerinde olduğu gibi mala dair tasavvurları da şekillenmiştir. Bu çalışmada İmam Şâfiî’nin sahip olduğu mal tasavvuru ve bu tasavvurun fürû-i fıkıh sahasında ne gibi neticeler doğurduğu, gerekli görülen bazı hususlarda sonraki dönem Şâfiî kaynaklarından da istifade edilerek tespit edilmeye çalışılmıştır. Neticede İmam Şâfiî’nin mal tasavvuru ortaya konacağından Şâfiî mezhebinin mal anlayışının ana çerçevesi bir arada görülebilecektir. Zira sonraki dönemlerde kaleme alınan Şâfiî kaynaklarına bakıldığında İmam Şâfiî’nin ortaya koyduğu mal anlayışının, bazı hususlarda değişim ve dönüşümler yaşanmakla beraber genel olarak takip edildiği tespit edilmiştir. İmam Şâfiî, mal anlayışı bakımından birçok âlime çeşitli açılardan muhalefet etmekle birlikte en esaslı değerlendirmelerini yönelttiği kesimlerden biri de Hanefî mezhebine müntesip âlimlerdir. Bundan dolayı İmam Şâfiî’nin mal anlayışının bağlamının tespit edilebilmesi için Hanefî mezhebinin erken dönemindeki mal tasavvurları üzerinde durulmuş ve gerekli yerlerde sonraki dönem çalışmalarından da istifade edilmiştir. Diğer birçok âlim gibi İmam Şâfiî de şeylerin mal sahasında değerlendirilebilmesi için çeşitli kriterler öne sürmüştür ki bunları; insanlara fayda sağlamak, şer‘an mübah olmak, satım akdine konu edilebilmek ve teaddî halinde hukuki koruma altına alınabilmek şeklinde özetlemek mümkündür. Koşulan bu şartlar dikkate alındığında satım akdine konu edilebilecek şer‘an mübah malî kıymet taşıyan şeylerin, mal kabul edildiği belirtilebilmektedir. İmam Şâfiî, şeylerin mal kabul edilebilmesi için bahsi geçen şartları koştuğundan dolayı Ehl-i kitabın mal edindiği domuz ve şarabı, onlar açısından da mal kabul etmeyerek hukuki koruma sağlamamış ve tahir olmayı bir mal kriteri olarak öne sürmüştür. Ancak tahâret vasfından yoksun olan köpek ve necis yağ gibi bazı şeyleri mal kabul etmediği halde ihtisas hakkına konu ederek bunlardan mübah yollarla istifade edilmesinin kapısını aralamıştır. Ayrıca mal sahasında değerlendirilebilmek için mübah bir malî kıymet taşımayı yeterli gördüğünden fiziki bir varlığa sahip olmayı şart koşmamıştır ki zikredilen bu gibi hususlar, İmam Şâfiî’nin mal tasavvuru bakımından Hanefî âlimlerden farklı bir kanaat benimsediği temel noktalardır. Onun bu anlayışında genel olarak naslara, özelde ise hadislere yaklaşım biçiminin etkili olduğu tespit edilmekte, benimsediği usûlî arka planın diğer bazı etkenlerle birlikte İmam Şâfiî’nin özellikle de Hanefî âlimlerden farklı bir mal anlayışı benimsemesine sebebiyet verdiği görülmektedir.

The foundational establishment of Imam Shafi'i's madhhab, which is attributed to him today, is attributed to his extensive pursuit of knowledge and research, which constituted a significant aspect of his life. As a result of these searches, his conceptions of property were shaped, as were his jurisprudential convictions. In this study, an attempt was made to determine Imam al-Shāfiʿī's conception of property and the consequences of this conception in the field of furu al fiqh. In certain instances, we have also endeavored to utilize Shafi'i sources from later periods. The study's findings reveal Imam Shāfi'ī's conception of property and the implications of this conception within the Shafi'i madhab's broader framework on property. A thorough examination of Shafi'i sources from subsequent eras reveals that Imam Shafi'i's conception of property is widely accepted, though it has undergone certain modifications and transformations in specific aspects. With respect to his conception of property, Imam Shāfi'ī has expressed opposition to numerous scholars from various perspectives. Notably, he directs a significant portion of his critiques at scholars belonging to the Hanafi madhhab. To understand Imam Shafi'i's perspective on property, it is necessary to examine the conceptions of property in the early period of the Hanafi madhab. To this aim, the study has also drawn upon later studies where relevant. Like many other scholars, Imam Shāfi'ī proposed various criteria for things to be considered as property. It is possible to summarize these criteria as providing benefit to people, being permissible in the Shari'ah, being subject to a contract of sale, and being legally protected in the event of transgression. When these conditions are taken into consideration, it can be stated that the things that can be subject to the contract of sale and that have a financial value that is permissible in the Shari'ah are considered as property. Imam Shāfi'ī did not provide legal protection for pork and wine, which the Ahl al-Bayt had taken as property, by not accepting them as such, since he stipulated the conditions previously mentioned for things to be considered property. Moreover, he advanced the principle of purity as a criterion for property. However, it should be noted that certain items lacking the taharah quality, such as dogs and impure oil, were subject to the right of specialization despite their exclusion from the definition of property. Consequently, Imam Shafi'i's legal framework permitted the utilization of these items in mubāh ways. In addition, since it is sufficient to have a permissible financial value in order to be considered as property, it did not stipulate the possession of a physical asset. These distinctions are pivotal in understanding Imam Shāfi'ī's differing perspective from that of the Hanafī scholars concerning the concept of property. His approach to the text in general and to hadiths in particular is found to be influential in this understanding. Together with other factors, Imam al-Shāfiʿī's procedural background is seen to have contributed to his distinctive interpretation of property, setting him apart from the Hanafī scholars.
The development of the concept of property and the analysis of the related provisions in the Shafi'i Madhhab
Keywords: Akit; Benefit; Compensation; Contract; Contract of Ijarah; Contract of Sale; Debt; Deyn; Hak; Hanafi Madhhab; Hanefî Mezhebi; Honorable; Imam Shāfi'ī; Imāmeyn; Islamic law; İcare Akdi; İhtisas; İmam Şâfiî; İmâmeyn; İslam hukuku; Mal; Menfaat; Muhterem; Property; Right; Satım Akdi; Shafi'i Madhhab; Specialization; Şâfiî Mezhebi; Tazmin